Anthropometric, Biomotor, and Physiological Factors for Indonesian Fencing Athletes Talent Identification - Dery Rimasa (Program Studi Ilmu Keolahragaan - Universitas Pendidikan Indonesia, 2021)
The development of fencing sports achievements through talent identification of fencing athletes does not appear to be an important process for coaches or clubs to help develop their programs. The purpose of this study was to determine the indicators involved in influencing the success factors of fencing athletes so that the results can be applied as development through a model for identifying Indonesian fencing athletes' talents. The population used in this study was 100 fencing sports experts in Indonesia that consist of 47 fencing athletes at the provincial level, 32 national athletes, 16 national coaches, and five national referees. The quantitative descriptive method was used in this research. Subjects filled the criteria weights in a questionnaire related to a factor scale that gave weight to the most important indicators in the anthropometric, biomotor, and physiological aspects. Statistical data processing is carried out through the Analytical Hierarchy Process (AHP) using expert choice software so that an intelligent model can be produced to identify the talents of fencing athletes in Indonesia based on the weighting of each criterion. The results show that the greatest contributing factors in determining the talents of prospective athletes are anthropometrics by 75%, biomotor factors by 13%, and physiological factors by 12%. Recognizing talent identification characteristics as consideration for successful athlete development will lead to a greater understanding of how the talent characteristics of athletes are developed.